Comparative Profile of S&T Research in lndia and China: A Quantitative Analysis of Publication Output - Gupta, B.M.; Dhawan, S.M.; Kharbanda, V.P.; Liming, Liang (DESIDOC Journal of Library & Information Technology, 2003)
The present study gives a comparative profile of lndia and China in terms of their growth in publication output, the priorities they have assigned to different fields in science and technology, and their collaboration with different countries during the last ten years from 1986-88 to 1995-97. http://dx.doi.org/10.14429/dbit.22.1.3552